Isolated Lateral Meniscal Tear in the Dog - Hulse, D.; Johnson, S. (Veterinary and Comparative Orthopaedics and Traumatology, 1988)
degenerative changes of the involved stifle joint associated with a “bucket handle” tear of the caudal body of the lateral meniscus. Surgical excision of the torn section of meniscus was beneficial in the first patient but this patient had persistant difficulty with the leg after exercise. Gross and microscopic pathology of the involved stifle in the second patient showed the meniscal lesion to be associated with severe cartilage fibrillation of the overlying lateral femoral condyle. As in human beings, the mechanism of injury may have been placement of the foot during vigorous external rotation of the femur with the stifle flexed. Extension of the limb from this position could have resulted in an isolated tear of the lateral meniscus.
Keywords: Meniscus; Canine; Injury